You may check your answer to make sure your answer is acurate.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
X^2+2X-1
5
5 + 2
5 - 1
25 + 10 - 1
35 - 1
34
I calculated this mentally. It took me less than a minute.
Given, f ( x ) = x 2 + 2 x − 1 f ( 5 ) = 5 2 + 2 × 5 − 1 = 2 5 + 1 0 − 1 = 3 4
Problem Loading...
Note Loading...
Set Loading...
f(x)= x 2 + 2 x − 1 and x = 5
so, x 2 + 2 x − 1
= 5 2 + 5 × 2 − 1
= 3 4